Risk Stratification of Coronary Heart Disease in Postmenopausal Women Using Framingham Scale in Eastern Nepal - Bajracharya, Sujeeta; Rai, Bijendra Kumar; Giri, Rajani; Joshi, Rinku (Medical Journal of Shree Birendra Hospital, 2018)
Introduction: Cardiovascular disease (CVD) is one of the leading causes of mortality and morbidity in both developed and developing countries. CVD risk rises to double fold in women after menopause. We aim to stratify menopausal women of our region for having coronary heart disease in next 10 years. Methods: One year cross sectional study was conducted in General Out Patient Department (GOPD) of a tertiary care centre of Eastern Nepal. The Standard ATP calculator was used and the relevant necessary data was introduced into the calculator and the automated result was collected. Results: Among 272 participants, above 50% had Framingham score 1 to 5%. And the risk was greater within first five years after menopause in 50 to 59 years of age group. Similarly, with advancing age and longer duration of menopause the risk became significantly higher. Conclusions: Besides the established risk factors for CVD, postmenopausal state is additional risk for women and this study emphasises this factor as risk of CVD even in our set up.